Condições e parâmetros para a determinação de conforto térmico em ambientes industriais do ramo metal mecânico - Pinto, Norma de Melo (2011)
There are two groups sharing research on thermal comfort. The first is devoted to research in environmental chambers held within an environment controlled by the investigator. The second group is dedicated to the research field in which the researcher does not interfere with environmental variables, personal and subjective, does not determine the activities to be carried on clothing and not to be used, however, notes, notes, estimates, and table or calculates the values of variables, indices and parameters of thermal comfort. The research is based on the series of International Standards ISO - International Organization for Standardization supriem that the lack of specific national legislation on the subject: thermal comfort. This study aimed to examine the existence of thermal comfort in the metal mechanic with employees performing their normal activities. For this, proceeded to assess the conditions and perceptions of the thermal environment, the survey was made of the influence of variables (metabolic rate, thermal clothing, air temperature, mean radiant temperature, speed and relative humidity) and the comfort subjective parameters (thermal sensation and preference) in May, August and November 2010. The industry investigated is located in the city of Ponta Grossa, Parana, Brazil. Based on the measurements of environmental variables, tables of personal variables, the calculation of the index of Predicted Mean Vote (PMV) and predicted percentage of dissatisfied (PPD), a collection of subjective parameters, the main results show that: a) the analyzed sectors provide heat and discomfort for employees who like a more refreshed, b) the PMV confirms that employees feel heat in industrial environments, c) the PMV model adopted by ISO 7730 (2005) applies to employees the thermal sensation with a coefficient of determination R ² = 0.81 d) in situations full of comfort, ie, PMV = 0 is I = 35.08% and there are a range of thermal acceptability (-0.5 < 0.5) with a maximum of 40.37% dissatisfied. Therefore, the outdoor environments have heat discomfort. There is a clear need for development of the Brazilian Code of thermal comfort, as well as conducting studies to determine the thermal insulation of work clothes and protective. The research points to the possibility of large errors in the use of international values of metabolic rate and confirms the need for studies to determine the metabolic rate according to the characteristics of the Brazilian man. The significant agreement of the PMV with the sensation reported by employees is not characteristic of the field.